FAKTOR-FAKTOR PENERIMAAN OBAT PADA PROGRAM PEMBERIAN OBAT PENCEGAHAN MASSAL (POPM) FILARIASIS - Sherly L. Kerjapy; Christiana R. Titaley; Marliyati Sanaky (PAMERI, 2019)
Filariasis is a systemic infection caused by adult filarial worms transmitted by mosquitoes. The first year MDA program in Kota Ambon (2009-2013) failed because the treatment target was less than 65%. This study aims to determine what are the factors of drug acceptance in Filariasis MDA program in working area of Waihaong and Air Salobar Public Health Center (PHC) in 2016. The type of research is cross sectional analytic. Amount of samples is 210 in each working area of PHC using cluster random sampling technique. The analysis used is Chi-Square test, with the variables studied are age, sex, occupation, education level, and knowledge level. The results showed in working area of Waihaong PHC, There was no correlation between age (p=0,705), sex (p=0,354), occupation (p=0,234), education level (p=0,742), knowledge (p=0,641) with Filariasis drug acceptance. In working area of Air Salobar PHC, there was a relation between sex (p<0.001), occupation (p=0.048), knowledge (p<0.001) with Filariasis drug acceptance, while no relation between age (p = 0.329) (p=0.082) with Filariasis drug acceptance.